2014
DOI: 10.1002/ca.22351
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the tracheobronchial tree: Anatomical and clinical significance

Abstract: Tracheobronchial variations can be found during routine bronchoscopy or computed tomography. Previous sources estimate an incidence of 1-12%; however, these variations are often asymptomatic. Symptomatic patients present typically with cough and lower respiratory tract infection. Knowledge and understanding of tracheobronchial variations have important implications for diagnosis of symptomatic patients and performing certain procedures, including bronchoscopy and endotracheal intubation. In this review, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 56 publications
2
24
0
3
Order By: Relevance
“…This preference for bronchial maldevelopment on the right side in the embryonic period create more space on the ipsilateral side. In the present study, true TB (the anomalous, displaced or rudimentary type as described by Wooten et al 20 ) or dimple was encountered significantly more often in the LPAS group among bilateral lung cases. This high prevalence supports the “space available” hypothesis described above.…”
Section: Discussionsupporting
confidence: 68%
“…This preference for bronchial maldevelopment on the right side in the embryonic period create more space on the ipsilateral side. In the present study, true TB (the anomalous, displaced or rudimentary type as described by Wooten et al 20 ) or dimple was encountered significantly more often in the LPAS group among bilateral lung cases. This high prevalence supports the “space available” hypothesis described above.…”
Section: Discussionsupporting
confidence: 68%
“…They suggested that this syndrome, also known as visceral heterotaxy, “is a severe variant of situs inversus which involves a complete breakdown in the classical asymmetry found in the abdominal viscera.” It is questionable whether the constellation of abnormal findings is a “severe variant of situs inversus.” Rather, the “breakdown in classical asymmetry” is of greatest significance, but this involves not only the abdominal but also the thoracic organs (Jacobs et al, ). Indeed, in the article immediately preceding the review relating to the inferior caval vein, in the same issue of the journal, another group of authors including two of those who collaborated with Spentzouris discussed the clinical significance of variations in tracheobronchial tree morphology (Wooten et al, ). These authors indicated that an isomeric arrangement of the bronchi is a key feature of so‐called heterotaxy, and rightly identified this feature as “a disorder of laterality.” Commenting on the correlation between abnormalities of the abdominal and thoracic organs, they suggested that left bronchial isomerism is found in three‐fifth of patients with “polysplenia syndrome,” and right bronchial isomerism in seven‐tenths of those with asplenia.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the atrial appendages are uniformly isomeric (Uemura et al, 1995). It is therefore unfortunate that Wooton and colleagues described polysplenia as associated with “left atrial isomerism” (Wooten et al, ). They described the association between asplenia syndrome and isomerism of the right atrial appendages correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous variations of lobar or segmental bronchial subdivisions have been described, but abnormal bronchi originating from the trachea or main bronchi remain rare conditions, with tracheal bronchus and ACB being the two most common tracheobronchial variants 1. ACB is an extremely rare condition (incidence 0.09–0.5%), usually asymptomatic and discovered incidentally 1.…”
mentioning
confidence: 99%
“…ACB is an extremely rare condition (incidence 0.09–0.5%), usually asymptomatic and discovered incidentally 1. ACBs are mostly blind, but can also lead to vestigial or ventilated parenchymal tissue, which must be searched for on CT scan.…”
mentioning
confidence: 99%